Philippine brittlestars (Echinodermata Ophiuroidea) described by R.Koehler (1922) A corrected and annotated list of type specimens. - Ahearn, Cynthia (Washington, D.C. Smithsonian Institution, 1992)
Smithsonian contributions to zoology ; no. 537
Keywords: Ophiuroidea--type specimens--Philippines.; Koehler, R. (René), b.1860. Ophiurans of the Philippine seas and adjacent waters